Mutation of ABCA4 gene as a cause of autosomal recessive form of Stargardt disease – case report - Spirkovska Mangeroska, Angelka; Pandilov, Stefan; Trpevska Shekerinov, Natasha; Goshevska Dashtevska, Emilija; Rushiti, Muhamedin; Muaremovska Kanzoska, Ljelja; Arsov, Todor (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2024)
Stargardt disease is the most common type of juvenile macular dystrophy. It is inherited autosomal recessively, although autosomal dominant forms have also been described. It affects both sexes equally, without racial predisposition. Patients experience a progressive deterioration of the macular region and loss of central vision, leading to legal blindness in the majority of affected individuals.In this paper, we describe the case of an 11-year-old boy who presented for an ophthalmological evaluation due to a progressive decrease in visual acuity. The fundoscopic examination supplemented with imaging ophthalmological methods were sufficient to establish a working diagnosis of Stargardt disease. The diagnosis was confirmed by genetic testing, a mutation of the ABCA4 gene, which is associated with this dystrophy. The importance of this case report is that it is one of the first documented cases of Stargardt disease with ABCA4 mutation in Macedonia
Keywords: Stargardt disease; autosomal recessive disease; optical coherence tomography; autofluorescence; macular dystrophy